2022
DOI: 10.1038/s41598-022-05034-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermal excitation signals in the inhomogeneous warm dense electron gas

Abstract: We investigate the emergence of electronic excitations from the inhomogeneous electronic structure at warm dense matter parameters based on first-principles calculations. The emerging modes are controlled by the imposed perturbation amplitude. They include satellite signals around the standard plasmon feature, transformation of plasmons to optical modes, and double-plasmon modes. These modes exhibit a pronounced dependence on the temperature. This makes them potentially invaluable for the diagnostics of plasma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Specifically, the interpretation of current XRTS experiments is solely based on LRT, [ 45 ] and the inference of important plasma parameters such as the electronic temperature T e is notoriously difficult. [ 44 ] In this context, Moldabekov et al [ 82 ] have recently suggested that the application of an external perturbation to generate inhomogeneous WDM samples on purpose leads to a modified experimental signal, that more strongly depends on T e . Naturally, the accurate theoretical description in this case will have to consider the mode‐coupling between this external potential and the XRTS probe, and the current LFC‐based theory is uniquely suited for this endeavour.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Specifically, the interpretation of current XRTS experiments is solely based on LRT, [ 45 ] and the inference of important plasma parameters such as the electronic temperature T e is notoriously difficult. [ 44 ] In this context, Moldabekov et al [ 82 ] have recently suggested that the application of an external perturbation to generate inhomogeneous WDM samples on purpose leads to a modified experimental signal, that more strongly depends on T e . Naturally, the accurate theoretical description in this case will have to consider the mode‐coupling between this external potential and the XRTS probe, and the current LFC‐based theory is uniquely suited for this endeavour.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The results at θ = 0.01 are presented for N = 38 electrons, and those at θ = 1.0 for N = 14 electrons. We note that finite-size effects have been extensively investigated in the literature and are expected to be small for these conditions. The corresponding cell lengths ( L ) are 10.839 and 7.7703 Bohr, respectively.…”
mentioning
confidence: 93%
“…In particular, the PIMC results have been used as the basis for a neural-net representation of the static electronic local field correction, and have become available as an analytical representation [69] that incorporates different limits [70]. In the mean time, these investigations have been extended to the nonlinear regime [41,[71][72][73][74][75], which, interestingly, is connected to the higher-order imaginary-time correlation functions [76].…”
Section: Introductionmentioning
confidence: 99%